How to Repurpose the University: A Resilience Lens on Sustainability Governance - Robinson, Zoe P.; Laycock Pedersen, Rebecca (Frontiers in Sustainability, 2021)
Universities have an important role in moving society towards a more sustainable future. However, this will require us to repurpose universities, reorienting and refocusing the different university domains (education, research, campus and outreach) towards sustainability. The governance structures and processes used to embed sustainability into the activities and operations of the institution are critical to achieving the required transformation. Our current university systems which are seen as contributing to socio-ecological system unsustainability are resilient to change due to slow variables such as organisational and sector-wide prevailing paradigms and culture. Therefore to repurpose a university requires us to destabilise our prevailing system, crossing a threshold into a new stable system of a ‘sustainable university’ across all its domains. This paper utilises an adaptation of Biggs et al’s. (2012) resilience principles for the governance of social-ecological systems to provide a framework to consider aspects of university governance for sustainability that can be utilised to repurpose universities towards sustainability, and destabilize unsustainable elements of the system. This paper draws out examples relating to sustainability governance within universities with regards to the four principles of i) managing diversity and redundancy, ii) managing connectivity, iii) managing slow variables and feedbacks, and iv) encouraging learning and experimentation within the context of complex adaptive systems. In this article, we have shown that using resilience in a non-normative way is possible (to decrease resilience of an unsustainable system), and that it can also be valuable to help understand how to shift organisational governance towards a particular end-state (in this case, university governance that advances sustainability). This paper provides an example of how to operationalise resilience principles of relevance to the resilience literature as well as providing a practical framework to guide higher education institution level governance for sustainability.